Ultrasonic Neuromodulation and Sonogenetics: A New Era for Neural Modulation - Wang, Songyun; Meng, Weilun; Ren, Zhongyuan; Li, Binxun; Zhu, Tongjian; Chen, Hui; Wang, Zhen; He, Bo; Zhao, Dongdong; Jiang, Hong (Frontiers in Physiology, 2020)
Noninvasive ultrasonic neural modulation (UNM), a noninvasive technique with enhanced spatial focus compared to conventional electrical neural modulation, has attracted much attention in recent decades and might become the mainstream regimen for neurological disorders. However, as ultrasonic bioeffects and its adjustments are still unclear, it remains difficult to be extensively applied for therapeutic purpose, much less in the setting of human skull. Hence to comprehensively understand the way ultrasound exerts bioeffects, we explored UNM from a basic perspective by illustrating the parameter settings and the underlying mechanisms. In addition, although the spatial resolution and precision of UNM are considerable, UNM is relatively nonspecific to tissue or cell type and shows very low specificity at the molecular level. Surprisingly in 2015, Ibsen and his colleagues first proposed the concept of sonogenetics, which combined UNM and mechanosensitive (MS) channel protein. This emerging approach is a valuable improvement, as it may markedly increase the precision and spatial resolution of UNM. It seemed to be an inspiring tool with high accuracy and specificity, however, little information about sonogenetics is currently available. Thus, in order to provide an overview of sonogenetics and prompt the researches on UNM, we summarized the potential mechanisms from a molecular level.